The Diagnostic Utility of Ambulatory EEG Following Nondiagnostic Epilepsy Monitoring Unit Admissions. Issue 2 (March 2019) - Fox, Jonah; Ajinkya, Shaun; Chopade, Pramod; Schmitt, Sarah
Abstract : Purpose: Epilepsy monitoring unit (EMU) admissions provide a definitive diagnosis for approximately three-quarters of patients. However, many patients do not receive a definitive diagnosis following EMU admission. Ambulatory EEG following nondiagnostic EMU admissions was evaluated as a means of providing a diagnosis for these patients. Methods: In this retrospective study, we performed a chart review of 62 pediatric and adult patients who had a 72-hour ambulatory EEG following a nondiagnostic EMU admission. Results: In total, there were 62 patients with nondiagnostic EMU admissions who subsequently underwent ambulatory EEG. Mean age was 33.8 (SD, 18.5) years. Forty-one patients (66.2%) were female and 46 (74.2%) adult. Fifty patients (80.7%) had an additional comorbid neurologic, somatoform, or psychiatric diagnoses. Of the original 62 patients, 32 (51.6%) had no events, 3 (4.8%) had events with and without EEG changes, 4 (6.5%) had only events with EEG changes, and 23 (37.1%) had only events without EEG changes. Ambulatory EEG thus provided clinically useful information in 30 (48.4%) cases, with 20 (66.7%) reaching diagnosis within 24 hours. Conclusions: Ambulatory EEG following a nondiagnostic EMU admission may yield positive results in approximately half of all patients. A substantial proportion of the events that were captured in this setting were without EEG changes. In the absence of video and supportive clinical information, these events not only may represent nonepileptic events but also could represent focal seizures without EEG changes. The presence of particular stressors in the home environment may explain why many patients, specifically those who are nonepileptic, had events relatively quickly following discharge.